Peran Pola Asuh Authoritative terhadap Self-Efficacy Akademik Dimediasi Vigor pada Remaja (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine the role of an authoritative parenting style on academic self-efficacy mediated by vigour. The research method used in this study is a quantitative method using a questionnaire for data collection and involving three types of measuring instruments to measure the three variables studied. The analysis technique used is a multiple linear regression technique using the SPSS Program to determine the mediators' role in the research. The measuring instrument in this study used (1) Parenting Styles and Dimension Questionnaire Short Version (PSDQ-Short Version) by only measuring authoritative parenting, (2) Level of Academic Self-Efficacy Scale, and (3) Shirom Melamed Vigor Measure. The three measuring instruments have been adapted into Indonesian and have good Cronbach alpha from the reliability testing results to be used as data collection tools. This research involved 116 teenage respondents who live in Jakarta and are active students. The study results show that there is a partial mediation of vigour in the role of authoritative parenting on academic self-efficacy. Thus, it can be concluded that H1 is accepted and H0 is rejected, where vigour can act as a mediator of authoritative parenting towards academic self-efficacy.